The DX and classification of ASDs: progress and pitfalls - Szatmari, Peter (Henry Stewart Talks, 2010)
History of terms, Types of ASD, ASD's common elements, What do we mean by 'spectrum'?, DSM-IV criteria for autism, Common mistakes in diagnosis, Clinical features and different uses of AS, DSM-IV criteria for AS, Problems with DSM-IV criteria, Is AS a valid disorder?, Differences between AS and autism, The outcome of autism, Autism behavior checklist, Sub-groups within autism pathway, PDD-NOS in DSM-IV, Prevalence rates, Proportion of autism to total ASD, Is PDD-NOS valid?, Problems with diagnostic system, Hierarchical approach to DX, ASD multiple spectra model
Reviewed at 2020/11/09, Archived at 2021/10/28